Índice de sustentabilidade: Um estudo aplicado no município de Marechal Cândido Rondon PR - Sontag, Anderson Giovane (2016)
In agriculture, sustainable proposals are still incipient minority and in certain social contexts, while recognizing that some regions have advanced in public policy implementations extension, technical assistance, agricultural research and financial input. Thus, for the direction of public policies, the measurement of sustainability is important for better monitoring in the municipalities. The objective of the research is to verify the degree of sustainability of farmers located in Macrozone of Manantial, in the city of Marechal Cândido Rondon - PR, watching the three dimensions: economic, environmental and social. Methodologically, it is an applied, quantitative research using statistical procedures and data collection, with the aid of electronic spreadsheets for formatting information in developing the sustainability index. The research is descriptive, aiming to describe certain population characteristics, establishing relationships between variables. In relation to the technical procedures, it is an action research, and a research method applied participatory nature, seeking the development of diagnostics for the municipality. In data collection the estimated population of 813 establishments and the sample represented by 185 farmers, with a sampling error of 6.5% and 95% confidence level. Applying a collection form divided into an initial section with the characterization of the respondent and property, as well as three subsections that include the pillars of sustainability, containing 43 environmental indicators, 18 economic and 33 social, with objective questions. The sustainability index in the region is 0.718, considers good. The best result is displayed in the social dimension with 0.778 index with emphasis on sanitation, electricity, access to communication and education. The environmental dimension has a lower index, considered medium grade. The research helps in the study of rural sustainability and their interactions in the different dimensions as well as the improvement of measurement models.